Proximal Femoral Fractures: Structure, Factors of Occurrence, and Treatment Principles (Literature Review) - Kalashnikov, A.V.; Lazarenko, Yu.V.; Kalashnikov, O.V. (TERRA ORTHOPAEDICA, 2022)
Summary. Proximal femoral fractures (PFF) constitute a significant medical and social problem, as they cause reasonable economic loss throughout the world. In 1990, the number of such traumas reached about 1.3 million, and by 2050, it is expected within 7-21 million cases. With the share of 17% in the structure of locomotion system traumas, they have large mortality and invalidity rate among the injured. The research analyzes international literature sources on incidence, factors of occurrence, mechanisms of development, and known classifications of PFF patients; basic methods of conservative and surgical treatment, as well as rehabilitation principles for this category are provided. We have found that, despite a large amount of literature, a clinical and diagnostic approach to the differentiated use of internal fixation for PFF is still not finally developed.